Evaluation of the opinion of healthcare organizers regarding the current situation in organization of glaucoma care in Ukraine - Melnyk, V. O.; Vasylieva, L. S. (Environment & Health, 2026)
The Aim. to investigate the opinion of health care organizers on the possibility of providing medical, diagnostic and preventive care to patients with glaucoma at the present time in Ukraine.Materials and methods. Evaluation of the results of a questionnaire of 290 health care organizers of private and public institutions of Ukraine. The work used bibliographic and analytical methods.Results. When asked about the quality and accessibility of ophthalmological care in health care institutions (HCPs) of Ukraine, more than 90% of respondents defined it as average and higher. 73% of respondents answered that the level of care for patients with glaucoma in Ukraine is lower than the world average.More than 85% of respondents answered that they use National and European clinical protocols in their practice. Less than 60% of respondents confirmed that there is surgical treatment of glaucoma used in their health care centers.The main factors influencing the high incidence of glaucoma were named by respondents as: insufficient attention of the population to their health (90.4%), insufficient awareness of the dangers of glaucoma and its consequences (81.9%), insufficient awareness of risk factors for glaucoma (78.3%); on the other hand, low accessibility of ophthalmological care was noted by only 15.7%.According to respondents, to improve glaucoma prevention, it is necessary to: strengthen preventive measures (87.6%), strengthen the work of family doctors on glaucoma (78.7%), increase public awareness of the dangers of glaucoma and its consequences (70.8%). At the same time, measures that will improve the quality and accessibility of medical care for glaucoma are considered: optimization of resource provision of health care facilities (73%), governmental control (60.7%), implementation of treatment standards (58.4%), improvement of technologies of preventive, diagnostic and treatment processes (42.7%).Conclusions. The study showed that the vast majority of respondents noted an insufficient level of care for patients with glaucoma in the institutions where they work, compared to the global one. The vast majority of respondents confirmed the use of approved clinical protocols and guidelines in their practice. Respondents considered the main shortcomings of organizing medical care for patients with glaucoma to be low awareness of the population and a preventive focus in providing care, insufficient material and technical base of health care facilities, and insufficient involvement in the processes of early detection of glaucoma in the primary care setting.
Keywords: ophthalmology; glaucoma; healthcare organization; healthcare institutions; glaucoma treatment and prevention